Translation of mathematical representation: characteristics of verbal representation unpacking - Dwi Rahmawati; Rahmad Bustanul Anwar (Intelektual Pustaka Media Utama, 2020)
The translation between mathematical representations was one of the indicators in understanding mathematical concepts. Understanding the things related to the process of student representation translation was very important in learning mathematics. One of the activities that plays a role in translation was unpacking the source. This study aimed to determine the characteristics of student activity in unpacking the source when doing the process of translational verbal representation to the graph. This research was using a qualitative research. The subject of this research were twenty mathematics education students. Selection of research subjects used purposive sampling. The data were collected by test and interview. The results showed that the characteristics of student activity in unpacking the source were two that are drawing scheme of verbal situation and interpreting verbal information with its own language. In addition, there were still many students failed in translation because of difficulties in unpacking the source. The results of this study were expected to add insight into learning to minimize student difficulties in unpacking the source.